2007
DOI: 10.1016/j.brainres.2006.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury induces oxidative injury, alterations in permeability and glutamine transport in cultured astrocytes

Abstract: The neurotoxicity of high levels of methylmercury (MeHg) is well established both in humans and experimental animals. Astrocytes accumulate MeHg and play a prominent role in mediating MeHg toxicity in the central nervous system (CNS). Although the precise mechanisms of MeHg neurotoxicity are ill-defined, oxidative stress and altered mitochondrial and cell membrane permeability appear to be critical factors in its pathogenesis. The present study examined the effects of MeHg treatment on oxidative injury, mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 75 publications
1
102
0
Order By: Relevance
“…These effects are explained by the direct inhibition of the transporter, the activity of which is suppressed by 10 µM methylmercury (see Fig. 3), i.e., the concentration used in the previous study [26]. The effects of cysteine and N-acetylcysteine in reversing the inhibition by mercurials correlates well with the use of these antioxidant compounds in mercury detoxification [4].…”
Section: Page 13 Of 30mentioning
confidence: 63%
See 2 more Smart Citations
“…These effects are explained by the direct inhibition of the transporter, the activity of which is suppressed by 10 µM methylmercury (see Fig. 3), i.e., the concentration used in the previous study [26]. The effects of cysteine and N-acetylcysteine in reversing the inhibition by mercurials correlates well with the use of these antioxidant compounds in mercury detoxification [4].…”
Section: Page 13 Of 30mentioning
confidence: 63%
“…It was previously reported that methylmercury inhibits the expression of the amino acid transporters SNAT1 and ASCT2 in astrocytes. However, this mechanism could not explain the effects caused at prolonged times of exposure to methylmercury [26]. These effects are explained by the direct inhibition of the transporter, the activity of which is suppressed by 10 µM methylmercury (see Fig.…”
Section: Page 13 Of 30mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the excitatory amino acid transporters (EAATs), the glutamate transporters, GLAST, GLT-1 and SNAT3 are the main players in provoking glutamate uptake into astrocytes in the CNS. Therefore, it was hypothesized that GLAST, GLT-1 and SNAT3 played an important role in maintaining GSH in the CNS (Yin et al 2007). In the current work, we found that the mRNA expression of the glutamate transporters was down-regulated obviously in CCl 4 alone.…”
Section: Antioxidant Activity Of D Glabra Leaves Extract (Dge) Againmentioning
confidence: 99%
“…98 The study of Nakagawa has shown that the total mercury concentrations in the hair of ordinary diseased people, including diabetes, were from 2.08 to 36.5 ppm; those values were considerably higher than that of healthy people of the same age-groups. 99 Organic or inorganic mercury compounds are well known to induce cellular damage in various cell types, such as renal cells, 92 astrocytes, 100 lymphoma cells, 101 human gingival fibroblast cells, 102 alveolar epithelial cells 103 and pancreatic islet β-cells. 104 Except for organic and inorganic forms of mercury toxicity, many studies focus on the vaccine preservative-thimerosal.…”
Section: Mercurymentioning
confidence: 99%